ISOLATION AND CHARACTERIZATION OF PHYTOCHEMICALS OF PASTINACA UMBROSA - Husniya Gara Mammadova; Siraceddin Veli Serkerov (Химия растительного сырья, 2022)
The Pastinaca genus belongs to Umbelliferae family. Pastinaca umbrosa grows widely in the north-west, west and center of Azerbaijan. In the present study, phytochemicals of the plants have been isolated and their structures have been elucidated. The mix of extractive substances was obtained by finely cutting the body of Pastinaca umbrosa, then drying in the room conditions (200 g) and extracting by acetone 3 times (3 days for each time). The acetone was filtered and evaporated on a water bath. The residue was a dark-brown resin (12 g, 6% yield). The resin (12 g) was dissolved in CHCl3 (50 mL) and chromatographed over a column of neutral Al2O3 with elution by hexane, hexane + benzen, benzene, benzene +chloroform, chloroform and chloroform+ etanol, in different ratios. The volume of each fraction was 100 mL. The separation and isolation process was carried out using column (silicagel) and thin layer chromatographic (TLC) methods. Structure elucidation of thepurified compounds were based on IR, UV, 1H and 13C-NMR data, in comparison with those reported in theprevious literatures. The isolated compounds from the aceton extracts of P. umbrosa were identified as esculetin 2.5%, scopoletin 4.5%, and umbelliferon 3.5%.